The duality of fear of missing out (FoMO) and university students' subjective well-being a phenomenological study - Gacmatan, Trisha Joyce L.; Pueblos, Vina S.; Ricote, Niña Francesca A.; Sadian-Cercado, Ruth Edisel Rylle B.; Villocino, Rica Angelica O. (2024)
Social media scrolling begets a psychosocial phenomenon called fear of missing out (FoMO), which became increasingly recognized in varying areas of investigation. However, as it is mostly focused as an online phenomenon, its existence in face-to-face settings is underrepresented. The present study explores university students' experiences and perceptions with Fear of Missing out (FoMO) in both online and offline contexts and its impact on their subjective well-being, specifically their mood, life goals, and life satisfaction. The findings of the present study revealed the distinct experiences of university students in relation to academic and social FoMO, stemming from their differing priorities. Various forms of coping mechanisms to reduce FoMO also surfaced, which were categorized into task-oriented, emotion-oriented, and avoidance-oriented coping strategies. Drawing upon Self-Determination Theory (SDT), the study reveals that while FoMO can negatively affect students' mood and satisfaction, it can also motivate them to engage in meaningful activities. The present study provides insights for the development of interventions to support students in managing FoMO and eventually improve their university experience.
Undergraduate thesis (B. A. Psychology) -- University of the Philippines, Tacloban.